Efektivitas Inisiasi Kultur Jaringan terhadap Pertumbuhan Mahkota Dewa (Phaleria macrocarpa) dengan Menambahkan Dosis Tiamin dan Asam Nikotinat pada Media Agar - Muhammad Zaenudin; Dian Nitami; Pahmi Husain; Khaerul Ihwan (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
The crown of the gods (Phaleria macrocarpa) is a medicinal plant that is well known to the public. Tissue culture is a plant propagation technique by isolating plant parts such as shoots, leaves, and buds, and growing these parts in aseptic artificial media that is rich in nutrients. Initiation is the taking and naming of sterile explants into the growing media. Tinamine and nicotinic acid (vitamins) are one of the elements needed by plants as antioxidants and launch metabolism in plants so that plants will quickly absorb the nutrients contained in the media. This study was conducted to determine the effectiveness of tissue culture initiation on the addition of thiamine and nicotinic acid (vitamins) doses. The research method used is the experimental method which was tested with ANSIRA (analysis of variance) at the level of 1% and 5%. The results of this study indicated that the addition of thiamine and nicotinic acid doses had an effect on the initiation of tissue culture, because at stem height F>F table 3.11 the results were significantly different. In the number of leaves parameter obtained F count 2.87 < from F table 3.11 then the result is significant. After further testing with BNJ (Honest Significant Difference) at the 5% test level, the results were significantly different.